Generational Transfer Among Family Businesses on the Fields of Reputation and Organizational Culture – Research Plan - Polster, Csilla (International Journal of Engineering and Management Sciences, 2017)
Aim: The aim of this paper is to generally introduce the topic, themes and relevance of the research on which my PhD thesis will be based. The research will focus on change of generations among Hungarian family businesses and deals with changes of leadership, organizational culture and core values, related to the management/owner succession. The research needs to apply knowledge from four disciplines ‒ PR, organizational culture, economic (family businesses) and leadership ‒ so it is multidisciplinary in nature. Following a current step of the research-process will be presented. Methodology: The Family Business Barometer results were applied for gaining information about the plans related to the future, generations, and so on of European Family Businesses. Then three Hungarian family businesses were interviewed in the frame of a panel-discussion organized by the Commercial and Industry Chamber in Győr-MosonSopron County. These three family businesses were the Borsodi Műhely, the Biotextima and the Leier. Findings: All in all between 2013 and 2016 most of the family businesses seemed to be confident about the future. In this aspect just a few family businesses were neutral in this time period. Unfortunately, there were family businesses who had a negative attitude for the future. The deliberate and detailed planning of the handover, the selection of a determined date for handover, the determination of the older generation to really do not interfere in affairs, the cohesive role of the family, family activities, the support from the family could lead to the effective change of generations.